A Query Conversion Scheme for Encrypted Cloud Databases - Hequn Xian; Jing Li; Xiuqing Lu (2013 International Conference on Information Technology and Applications, 2013)
Encryption is an effective way of protecting sensitive data that have been outsourced in the cloud computing environment. But it is computationally expensive for the database management system to carry out SQL queries against the encrypted data. A query conversion scheme is presented which converts traditional database queries to encryption specific versions so that the queries can be directly executed on the cloud server. This scheme dramatically increases the efficiency of query processing in encrypted cloud databases, and it provides high transparency for end users by introducing a SQL gateway to the user applications and the cloud server.